Metal subcellular partitioning determines excretion pathways and sensitivity to cadmium toxicity in two marine fish species. (February 2019) - Le Croizier, Gaël; Lacroix, Camille; Artigaud, Sébastien; Le Floch, Stéphane; Munaron, Jean-Marie; Raffray, Jean; Penicaud, Virginie; Rouget, Marie-Laure; Laë, Raymond; Tito De Morais, Luis
Abstract: Subcellular cadmium (Cd) partitioning was investigated in the liver of two marine fish species, the European sea bass Dicentrarchus labrax and the Senegalese sole Solea senegalensis, dietary exposed to an environmentally realistic Cd dose for two months followed by a two-month depuration. The two species displayed different handling strategies during the depuration period. Cd was largely bound to detoxifying fractions such as heat stable proteins (HSP) including metallothioneins (MT) in sea bass, while Cd was more linked to sensitive fractions such as organelles in sole. Whole liver concentrations and subcellular partitioning were also determined for essential elements. The greatest impairment of essential metal homeostasis due to Cd exposure was found in sole. These elements followed the Cd partitioning pattern, suggesting that they are involved in antioxidant responses against Cd toxicity. Cd consumption diminished sole growth in terms of body weight, probably due to lipid storage impairment. The contrasting partitioning patterns showed by the two species might imply different pathways for Cd elimination from the liver. In sea bass, MT-bound Cd would be excreted through bile or released into blood, crossing the cell membrane via a protein transporter. In sole, MRG-bound Cd would be sequestered by organelles before being released into the blood via vesicular exocytosis. These distinct strategies in cellular Cd handling in the liver might account for differential sensitivity to Cd toxicity and differential Cd excretion pathways between the two marine fish species. Graphical abstract: Highlights: Sea bass and sole displayed different Cd subcellular partitioning in the liver. Cd was largely bound to metallothionein-like proteins in the sea bass liver. Cd was mainly linked to organelles in the sole liver. Essential metals followed the Cd partitioning pattern in hepatic cells. Handling strategies might account for sensitivity and Cd excretion.